Consumer Behavior on Purchasing of Fresh Oyster Mushrooms in Kraksaan Probolinggo - Novita Lidyana; Dyah Ayu Perwitasari (Medikun Publisher, 2024)
This research aims to identify characteristics and consumer behavior related to fresh oyster mushrooms at Semampir Market, Kabupaten Probolinggo. Conducted from June to August 2021, the study employs the Fishbein Analysis Model to analyze consumer attitudes based on beliefs about fresh oyster mushrooms. Semampir Market was chosen due to its status as a prominent hub for fresh oyster mushroom sales, attracting consumers in Kabupaten Probolinggo. Findings reveal that 92% of consumers are female, with the majority falling within the 35-44 age range. Educationally, most consumers have completed high school, though some are still students, indicating potential for educational enhancement. Consumer income analysis indicates that 50% fall within the 1.5 million – 3 million range, and 22% earn between 3 million – 5 million. Despite diverse income levels, consumers exhibit positive attitudes toward purchasing fresh oyster mushrooms at Semampir Market, with an overall score of 4.104, indicating a